Differences in milk production and lactation-related behaviours in breeding does housed in individual enriched cages and part-time systems - Ramón-Moragues, Adrián; Martínez-Paredes, Eugenio; Villagrá, Arantxa (World Rabbit Science Association, 2022)
The effect of collective rearing of breeding does was assessed in terms of milk yield and behavioural patterns. A total of 40 breeding does were used, 20 of them housed in individual cages (50x90x50 cm) and 20 in a collective system in groups of 4 rabbits (200x90x50 cm) since 14 days post-partum until 28 days, in which weaning took place. Milk production was assessed during the 1st and 2nd parturition, finding differences between groups only in the second one, when does from the part-time system produced less milk. Straw was offered to animals as environmental enrichment ant its consumption was assessed, finding that does reduced straw consumption in the part-time system compared to individual cages. This effect might be related to the presence of social stimuli. In addition, the number of kits stolen by does from alien nests was higher during the first days after grouping, achieving 60% of the kits.